Experimental evidence of multiple ecosystem services and disservices provided by ecological intensification in Mediterranean agro‐ecosystems. Issue 10 (2nd August 2020) - Segre, Hila; Segoli, Michal; Carmel, Yohay; Shwartz, Assaf
Abstract: Intensifying agricultural production in sustainable ways is pivotal to increasing food production while reducing environmental impacts. Ecological intensification is based on managing organisms that provide services underlying crop production to simultaneously intensify agricultural production and increase biodiversity. However, few studies address the interactions and trade‐offs between biodiversity, multiple ecosystem services and crop production. We experimentally quantified the effect of uncultivated field margins, a prominent practice of ecological intensification, on agricultural production, biodiversity, as well as on multiple ecosystem services and disservices, in an intensive Mediterranean agro‐ecosystem. We used a split‐plot design and sampled butterflies, rodent and arthropod pests, arthropod natural enemies (both parasitoids and predators), weeds, damage to crop and crop yield in different distances into the field in 3 tomato and 11 wheat crops along the growing season. Field margins increased natural enemy densities, reduced pest‐damage to crop and consequently increased yield in tomato crops. Notably, we found that pest control by one predator species was dominant in the field centre, whereas parasitoid natural enemies were confined to the field edges. Pest control was more prominent in the late crop‐stage compared to early season sampling and field margins increased weed control in tomato crops by reducing weed cover. Field margins increased natural enemy densities in wheat at the beginning of the season, but effects on arthropod pests were inconsistent. Field margins slightly increased weed cover, but had no impact on rodent densities and total yield. Butterfly abundance, but not richness, was positively affected by vegetated field margins. Synthesis and applications . Promoting ecological intensification requires a holistic approach that considers the complex relationships among ecological and economic aspects of agro‐ecosystems. We found that ecologically intensified field margins provided pest and weed control in the highly intensive tomato crop, yet they increased weed cover in wheat, which could potentially restrict yields at the field scale. Farmers' guidelines should therefore consider the interactive effects of multiple services on a variety of crops. Moreover, biodiversity components that do not provide crop production services should be independently targeted (e.g. by sowing plants that provide food resources). Abstract : Promoting ecological intensification requires a holistic approach that considers the complex relationships among ecological and economic aspects of agro‐ecosystems. We found that ecologically intensified field margins provided pest and weed control in the highly intensive tomato crop, yet they increased weed cover in wheat, which could potentially restrict yields at the field scale. Farmers' guidelines should therefore consider the interactive effects of multiple services on a variety of crops. Moreover, biodiversity components that do not provide crop production services should be independently targeted (e.g. by sowing plants that provide food resources).